(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Fertility of Plodia interpunctella (Hubner), Cadra cautella (Walker), Ephestia kuehniella Zeller has been evaluated using ten couples coming from fasting larvae of III instar. Their progeny has been compared to that of 10 referential couples, coming from larvae developed on artificial diet until the complete maturity. The fertility of adults is significantly lower than the relatives couples of reference. About sex ratio, the number of females is more than double towards the number of males, in every couple of reference. The number of females increased in descent of couples subjected to alimentary stress, both for C. cautella and for E. kuehniella, while for P. interpunctella the relation among males and females was similar to the descent of referential couples. Larvae coming from adults developed from III instar larvae have been isolated in two groups: a batch of 50 larvae has been submitted to forced fasting, another batch has fed regularly. Couples of adults, coming from III instar larvae subjected to starvation, gave life to a number of larvae that could be compared with their parents progeny. Larvae born from parents subjected to starvation but fed regularly until the end of larval stadium, gave life to adults, whose progeny is possible to compare with the one of referential couples. An adequate feeding can nullify the effects on fertility coming from alimentary stress subjected by parents.